Exploring Breast Cancer Dynamics: Understanding Risk Factors, Health Behaviors, and Treatment Trends among Women in Derna, Libya - Arig Alyasir; Aisha Bojazyah; Ilham Elyseir (AlQalam Journal of Medical and Applied Sciences, 2024)
Breast cancer poses a significant global health challenge, being the second most common cancer among women and a leading cause of cancer-related deaths. This research aims to investigate the multifaceted dimensions of breast cancer, from risk factors to diagnostic methods and treatments. A comprehensive analysis of 109 Libyan females who lived in Derna, utilizing an online questionnaire disseminated through social media platforms. In this study, 23% were diagnosed with breast cancer, while 77% were controls. Higher breast cancer incidence was observed among younger individuals (26-34 years) and those who were overweight. Most cases were from central Derna, were university graduates, employed, married, and had high incomes. Key risk factors included positive family history (20%), oral contraceptive use (4%), and hormone replacement therapy (8%). Higher rates of gynecologist visits, clinical breast examinations, and breast cancer screening were noted in the case group. The majority of cases were diagnosed at Stage III, primarily through tissue biopsy, with many opting for combined surgery and radiotherapy. In conclusion, bridging the gaps in knowledge about breast cancer risk factors, early detection methods, and treatments is crucial for advancing comprehensive cancer management and improving patient outcomes. Continued research and personalized treatment approaches are essential for the evolving landscape of breast cancer care. سرطان الثدي، الذي ينتشر عالمياً ويعتبر الثاني الأكثر شيوعاً بين النساء، يشكل مشكلة صحية عامة مهمة. فهم دينامياته المتعددة، بما في ذلك عوامل الخطر وطرق الكشف وخيارات العلاج، أمر بالغ الأهمية للإدارة الفعالة. قامت هذه الدراسة، التي أُجريت بين النساء الليبيات، بالتحقيق في هذه الجوانب، مع التركيز على 109 مشاركة في درنة. أظهرت النتائج أن 23٪ من المجموعة كانت تعاني من سرطان الثدي، وكانت النساء الأصغر سناً (26-34 عامًا) وأولئك الذين يصنفون على أنهم زائدو الوزن يظهرون نسبة أعلى من الإصابة. معظم الحالات كانت تقيم في وسط درنة، وكانت خريجات الجامعات، وموظفات، ومتزوجات، وكانت لديهن دخلاً عالياً. وكانت العوامل الرئيسية للخطر تشمل التاريخ العائلي الإيجابي، واستخدام وسائل منع الحمل الفموية، وعلاج الهرمونات البديلة. وكانت الممارسات الصحية مثل زيارات طبيب النساء وفحص سرطان الثدي أكثر انتشاراً بين الحالات مقارنة بالضوابط. كانت الطرق التشخيصية تتضمن بشكل أساسي بيوبسيا الأنسجة، مع تشخيص العديد من الحالات في مراحل متأخرة. وتباينت الخيارات العلاجية، مع نسبة كبيرة تختار الجراحة المشتركة والعلاج الإشعاعي. تؤكد الدراسة أهمية استراتيجيات الكشف المبكر والتدخلات المصممة خصيصاً لإدارة سرطان الثدي. وهناك حاجة لإجراء مزيد من الأبحاث لتعزيز الوعي وتحسين استراتيجيات الإدارة لهذا التحدي الصحي العالمي